If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 43 + -4x = 2 + -8x + 5 Reorder the terms: 43 + 2x + -4x = 2 + -8x + 5 Combine like terms: 2x + -4x = -2x 43 + -2x = 2 + -8x + 5 Reorder the terms: 43 + -2x = 2 + 5 + -8x Combine like terms: 2 + 5 = 7 43 + -2x = 7 + -8x Solving 43 + -2x = 7 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 43 + -2x + 8x = 7 + -8x + 8x Combine like terms: -2x + 8x = 6x 43 + 6x = 7 + -8x + 8x Combine like terms: -8x + 8x = 0 43 + 6x = 7 + 0 43 + 6x = 7 Add '-43' to each side of the equation. 43 + -43 + 6x = 7 + -43 Combine like terms: 43 + -43 = 0 0 + 6x = 7 + -43 6x = 7 + -43 Combine like terms: 7 + -43 = -36 6x = -36 Divide each side by '6'. x = -6 Simplifying x = -6
| (U-8)(u+2)= | | -1y-1+y=-1 | | b+17=31 | | -3.3k=-19.8 | | 40+80=40+90 | | y-21=-4 | | 46.9=6.7a | | -3+4x=9x+12 | | -2(b-4)=-b+8 | | 19=4c+8c | | -5=7+2x | | 40(x+2)-32x=200 | | s+9=-13 | | 4(6-z)+z=21 | | 19-2z=6(7z-5) | | 3x-6+4+130+8x+4=180 | | 5x+20-5=3x-18+1 | | 3*x+1=3x+3 | | 2(9-8y)=-30 | | 7=w-5 | | (3x+28)+(12x-28)=180 | | -6(8x+9)=23 | | -14=r-5 | | 4x+20=5x | | 9x^2-2x-1=0 | | -2(1+5s)=-25 | | -3-4(1+7r)=-15 | | 9(-8+3x)=63 | | (y-4)-(y+5)=7y | | 5a-7a=19 | | -4(7+4x)=84 | | -9s+8+4=27 |